Intravenous Foreign Body at the Hand: Case Report - Couceiro, Jose; Garcia-Valladares, Elena; Fernandez-Divar, Jose; Sanchez-Crespo, Manuel; Ayala, Higinio; Canto, Fernanado Del (The Surgery Journal, 2022)
Intravenous foreign bodies following trauma to the hand are relatively uncommon with sparse reports of this condition being published in the literature. They have been reported to migrate as far as the thoracic cavity and the heart. In the following case report, we describe a case of an intravenous foreign body following hand trauma, and the treatment and potential complications are also discussed.
Keywords: intravenous; foreign body; hand